A multi-spectroscopic study on the interaction of food polyphenols with a bioactive gluten peptide: From chemistry to biological implications. (30th November 2019) - Dias, Ricardo; Brás, Natércia F.; Pérez-Gregorio, Maria; Fernandes, Iva; Mateus, Nuno; Freitas, Victor
Highlights: Polyphenol-peptide binding occurs through an entropy-driven hydrophobic effect. Polyphenol-peptide binding depends on polyphenol substitution pattern and polymerization. Polyphenols bound to 32-mer Tyr, Leu and Phe containing domains. Procyanidins B3 and C2 reduced the 32-mer transepithelial translocation in vitro . In addition to peptide binding, other regulatory mechanisms are involved. Abstract: This study aims to exploit the molecular and cellular mechanisms concerning the functionality of dietary polyphenols (catechin, procyanidin B3, procyanidin C2, epigallocatechin and epigallocatechin gallate) in a nutritional context to prevent Celiac Disease (CD). In that sense, the interaction between the main CD bioactive peptide (32-mer peptide) and some polyphenols was fully characterized at the intestinal level under near physiological conditions by means of different spectroscopic techniques and dynamic simulations. Accordingly, it is proposed that the primarily polyphenol-binding sites on the 32-mer peptide correspond to leucine, tyrosine and phenylalanine containing domains being this interaction entropy-driven. Although procyanidin B3 and trimer C2 had a similar low-affinity constant at 310 K, both procyanidins were able to reduce the 32-mer peptide apical-to-basolateral translocation in in vitro simulated intestinal epithelial barrier thus prospecting the occurrence of additional and still unexplored regulatory mechanisms by which dietary polyphenols might modulate the transepithelial transport of CD bioactive peptides.